THE INFLUENCE OF RELAXATION TECHNIQUE ON THE LEVEL OF ANXIETY IN PRE-CIRCUMCISION SURGERY - Agus Wantoro; Agus Sulistyowati (Nurse and Health: Jurnal Keperawatan, 2021)
Background: Anxiety in children who will undergo circumcision is recognized as part of the trauma experienced by children due to actions that are considered dangerous for themselves. Excessive anxiety in pre circumcision can be prevented through one of the techniques of deep breathing relaxation. Objectives: The purpose of this study was to determine the effect of relaxation techniques on anxiety in patients with pre-circumcision surgery at the Circumcised House Sarirogo, Sidoarjo. Design: The population target was all of the patient for the circumcision in the Circumcised House of Sarirogo, Sidoarjo as many as 28 respondents. The technique sampling in this study used Consecutive Sampling technique. The sample size obtained 22 respondents. The independent variable in this study is relaxation techniques and the dependent variable is the anxiety of pre-circumcision patients. Data were taken using a questionnaire about anxiety given to respondents before and after relaxation techniques were carried out on 1–15 September 2020. This study used Wilcoxon Statistic Test and this research design used a pre-experimental one group pretest-posttest design. Results: The results showed as many as 7 respondents (31.8%) experienced severe anxiety levels before the relaxation technique was applied, while after being given relaxation techniques, the respondent's anxiety level decreased to 3 respondents (13.6%o). Based on statistical analysis result, it found that relaxation technique affects to the level of anxiety positively (p-value = .000). Conclusion: Relaxation techniques in nursing interventions are to divert or distance the client's attention to something that is being faced. While the benefits of this technique, that is, so that someone who receives this technique feels more comfortable, relaxed, and feels in a pleasant position.